2018
DOI: 10.24925/turjaf.v6i1.107-111.1710
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of RAPD Markers to Analyse the Genetic Diversity among Sunflower (Helianthus annuus L.) Genotypes

Abstract: Genetic diversity estimation among different species is an important tool for genetic improvement to maximize the yield, desirable quality, wider adaptation, pest and insect resistance that ultimately boosting traditional plant breeding methods. The most efficient way of diversity estimation is application of molecular markers. In this study, twenty random amplified polymorphic DNA (RAPD) primers were utilized to estimate the genetic diversity between ten sunflower genotypes. Overall 227 bands were amplified b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Genetic divergence analysis is used for polymorphism, inbreeding, assessment, assortment, and recombination to attain plant perfection, and is amongst the main aspects for defining accomplished inbreeding. Genetic divergence analysis is considered a very important method for the development of new cultivars based on genetic distance and similarities [ 120 , 121 ]. For genetic studies landraces are a significant source, for example, a wheat landrace kept in data bank comprises broader genetic variance and is a valuable basis for stress resistance as it contains cultivars adjustable to diverse environmental stress [ 122 ].…”
Section: Approaches To Combat Climate Changesmentioning
confidence: 99%
“…Genetic divergence analysis is used for polymorphism, inbreeding, assessment, assortment, and recombination to attain plant perfection, and is amongst the main aspects for defining accomplished inbreeding. Genetic divergence analysis is considered a very important method for the development of new cultivars based on genetic distance and similarities [ 120 , 121 ]. For genetic studies landraces are a significant source, for example, a wheat landrace kept in data bank comprises broader genetic variance and is a valuable basis for stress resistance as it contains cultivars adjustable to diverse environmental stress [ 122 ].…”
Section: Approaches To Combat Climate Changesmentioning
confidence: 99%
“…Umesh Kanna (2001) also observed the same trend in Madhuca latifolia. Raza et al (2018) [32] reported that, the 86.34% polymorphism and 13.65% monomorphism was observed using twenty RAPD markers to estimate the genetic diversity among ten sunflower genotypes. All the accessions originated from the CPTs selected in Tamil Nadu were grouped into cluster-I.…”
Section: Resultsmentioning
confidence: 99%
“…To the high proportion of variance between 14 genetic types of sunflower. The results reached by [25] indicated that when they studied 10 strains of sunflower using RAPD indicators, 20 primers were used to know the genetic changes and kinship between strains and through the analysis based on the results of RAPD, which included the strains in two main groups.…”
Section: Introductionmentioning
confidence: 99%